The Algerian-Italian relations: A strategic partnership in a turbulent geopolitical context (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Over the past twenty-five years, Algerian-Italian relations have evolved into one of the most structured and resilient bilateral partnerships linking North Africa and the European Union. The 2003 Treaty of Friendship institutionalized political dialogue and economic cooperation, with energy interdependence – anchored in the TransMed pipeline – forming the core of mutual interests. Beyond hydrocarbons, historical ties and sustained high-level exchanges have helped manage political divergences and preserve diplomatic continuity. Yet the partnership remains asymmetrical and sectorial: Italy’s policies are framed by EU and NATO commitments, while Algeria upholds principles of sovereignty and non-interference. Consequently, collaboration is more consistent in the economic than in the security domains. Algerian-Italian relations thus reveal the asymmetries of North Africa-EU interaction, where pragmatic cooperation coexists with enduring hierarchies and the interplay of authoritarian resilience and democratic pragmatism.
Keywords: Algeria; Italy; Energy; Security Interests; Bilateral relations